2024
DOI: 10.3389/fnut.2024.1335831
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple serum minerals and vitamins with metabolic dysfunction-associated fatty liver disease in US adults: National Health and Nutrition Examination Survey 2017–2018

Peisen Guo,
Jiahui Yu

Abstract: BackgroundDespite the rapid increase in the global prevalence of Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD), there are no approved therapeutic drugs for MAFLD yet. Nutrient supplementation might mitigate the risk of MAFLD. It is more typical for individuals to consume multiple nutrients simultaneously. However, the studies exploring the combined effects of multiple nutrients on MAFLD are limited. This study aimed to investigate the relationship between both individual nutrients and their comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Studies have shown that high dietary selenium intake increases the risk of MAFLD by modulating insulin biosynthesis and secretion dysregulation as well as stimulating glucagon secretion, insulin resistance and dyslipidemia ( 62 ). Reducing the ratio of Se and vitamin E, or not supplementing them at all, may reduce the prevalence of MAFLD ( 63 ). Patients with MAFLD consume more vitamin E in their daily diet than healthy controls, so increased vitamin E may be positively associated with MAFLD ( 64 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%
“…Studies have shown that high dietary selenium intake increases the risk of MAFLD by modulating insulin biosynthesis and secretion dysregulation as well as stimulating glucagon secretion, insulin resistance and dyslipidemia ( 62 ). Reducing the ratio of Se and vitamin E, or not supplementing them at all, may reduce the prevalence of MAFLD ( 63 ). Patients with MAFLD consume more vitamin E in their daily diet than healthy controls, so increased vitamin E may be positively associated with MAFLD ( 64 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%